-4(2w+9)-12=-96

Simple and best practice solution for -4(2w+9)-12=-96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2w+9)-12=-96 equation:



-4(2w+9)-12=-96
We move all terms to the left:
-4(2w+9)-12-(-96)=0
We add all the numbers together, and all the variables
-4(2w+9)+84=0
We multiply parentheses
-8w-36+84=0
We add all the numbers together, and all the variables
-8w+48=0
We move all terms containing w to the left, all other terms to the right
-8w=-48
w=-48/-8
w=+6

See similar equations:

| 5(x-1)=25* | | 5=10+x/5 | | -2(x+3)=-40* | | 3(p-7)-5=4 | | 26x+9x=14 | | 16(x+3)=14(x+6) | | -5(x+11)-13=12 | | 20x+25x=335 | | 3y+2=-4+3y | | -9(4x-8)=17 | | 45=−9(−x+6) | | -12+5h=2h+3 | | 2d=28d= | | 45=−9(−x+6 | | 7x-5(4x)=-13 | | 2.5x+0.5x=12 | | 4m+9=–7+8m | | -12+5h=3h+3 | | 38x=8 | | 9=2r−–3 | | 3/p+11=14 | | y=2*3 | | 8x+(93-3)=400 | | 5y+7=2y-14 | | 10-x4x+4=40 | | t2+26t=27 | | 19+n=33 | | 5k2–60=-20k | | 7m+120=11m | | -4(x+4)+2x=16 | | w6=5 | | -02-2)=Y2-5-2y2 |

Equations solver categories